On the genus Sabidius Strelzov, 1973 (Annelida: Paraonidae), with a redescription of the type species and the description of a new species. - Natália Ranauro; Rômulo Barroso; Paulo Cesar Paiva; João Miguel de Matos Nogueira (PLoS ONE, 2020)
Two species of Sabidius Strelzov, 1973 were collected during a benthic survey, from 10-3,000 m deep, in Espírito Santo Basin, off southeastern Brazilian coast. Those species are S. cornatus (Hartman, 1965) and S. antennatus sp. nov. The genus Sabidius was monotypic until the present study, in which a new species is proposed, together with a redescription of the type species, with expansion of the geographic distribution of the genus and of the type species. The diagnostic feature of the genus is the morphology of prostomium, with crested anterior margin. The main feature that differentiates the two species within the genus is the presence/absence of a median antenna, which is present in the new species described in the present study and absent in Sabidius cornatus.